2003
DOI: 10.1038/sj.ijo.0802296
|View full text |Cite
|
Sign up to set email alerts
|

Changes in abdominal subcutaneous fat water content with rapid weight loss and long-term weight maintenance in abdominally obese men and women

Abstract: OBJECTIVE: Insulin resistance decreases blood flow and volume in fat tissue. We hypothesised that fat tissue nutritive blood flow and volume, and thereby water content, would increase during weight loss and weight maintenance in obese persons. DESIGN: Longitudinal clinical intervention with a 9-week very-low-calorie diet (VLCD) followed by one year of weight maintenance. SUBJECTS: Obese men (n ¼ 13) and women (n ¼ 14) with the metabolic syndrome. MEASUREMENTS: Water content of abdominal subcutaneous fat tissue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
51
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(56 citation statements)
references
References 30 publications
4
51
0
Order By: Relevance
“…529,[536][537][538] (1+) Weight loss by any means improves insulin sensitivity in adults with type 2 diabetes or the metabolic syndrome. 270,472,475,529,[539][540][541][542][543][544] (1+) Dietary intervention is pivotal to the achievement of weight loss, while exercise and behavioural programmes or drug therapies are adjunctive therapies and alone do not achieve outcomes equivalent to those that include a dietary intervention component. 233,474,477 Diet-alone weight loss strategies leading to mean weight losses of 9 kg with various dietary programmes are associated with a mean reduction of 2.7% in absolute HbA1c in subjects with type 2 diabetes.…”
Section: Energy Balancementioning
confidence: 99%
“…529,[536][537][538] (1+) Weight loss by any means improves insulin sensitivity in adults with type 2 diabetes or the metabolic syndrome. 270,472,475,529,[539][540][541][542][543][544] (1+) Dietary intervention is pivotal to the achievement of weight loss, while exercise and behavioural programmes or drug therapies are adjunctive therapies and alone do not achieve outcomes equivalent to those that include a dietary intervention component. 233,474,477 Diet-alone weight loss strategies leading to mean weight losses of 9 kg with various dietary programmes are associated with a mean reduction of 2.7% in absolute HbA1c in subjects with type 2 diabetes.…”
Section: Energy Balancementioning
confidence: 99%
“…We have found only short-term studies, relative to rapid weight loss, reported in the literature. It has been reported that water content, a potential reflection of nutritive blood flow (112,142), was increased after a 15.6-kg weight loss over a 9-wk period, suggesting that improved insulin sensitivity may contribute to improve ATBF (110). Recently, rapid weight loss in healthy obese subjects on very low caloric intake diets induced no modification of ATBF when expressed per gram of mass (181).…”
Section: ·Minmentioning
confidence: 99%
“…The significant reduction in the WC measurements of the intervention group may suggest an improvement in the metabolic profile, as demonstrated by Laaksonen et al 26 , who studied patients with the metabolic syndrome following a hypocaloric diet during nine weeks and maintaining the weight for one year; they found that weight loss reduced body fat and waist circumference, which correlated with higher insulin sensitivity. According to Ravensbergen et al 7 and Martins & Marinho 27 , WC is significantly associated with hypertension and hypercholesterolemia.…”
Section: Discussionmentioning
confidence: 73%